'Factivism': A New Configuration of Humanitarian Reason. Issue 1 (2nd January 2017) - Mitchell, Katharyne
ABSTRACT: New actors and ideas about poverty management and humanitarian assistance have arisen in recent years. The underlying context of this shift includes a growing awareness of the limitations and failures of both military forms of humanitarian intervention and unfettered market-based solutions to aid and development. This paper explores the particular form that global humanitarianism is taking in this millennial context. I argue that a new configuration of humanitarian reason is emerging that draws on both neoliberal and pastoral rationalities of governance. The former can be associated with efficiency, transparency, and quantitative evidence, while the latter is articulated with individual compassion, devotion, and Christian duty. Using the celebrity humanitarian Bono and his rhetoric of 'factivism' as an illustrative example, the paper explores the way that this message is transmitted through geosocial discourses and networks. It indicates some of the ways that the personal and media dissemination of this new ideology of charismatic, yet rational care helps to weave pastoral rationalities into forms of political authority.